Sanitation practices and health outcomes among undergraduates in a tertiary institution: a cross-sectional study in the middle belt - Oye, Oshimagye Victor; Abraham, Joshua Msonter; Abraham, Ochanya Olivia; Martins, Alfred Damilola (International Journal Of Community Medicine And Public Health, 2025)
Background: Globally, inadequate sanitation behaviours have accounted for numerous health risks. World Health Organization (WHO) reports that poor sanitation contributes to spread of diseases such as diarrhoea, cholera, and typhoid, which are responsible for a significant burden of morbidity and mortality, particularly in low- and middle-income countries in the world. Methods: A cross-sectional descriptive study was carried at Benue State University, Makurdi, Nigeria, with a multistage sampling technique. Data was collected and analysed using SPSS (version 20.0). Results: We observed insufficient handwashing facilities at strategic locations on campus (86.6), with inadequate awareness and education on sanitation behaviours, accounting for the improper sanitation among the students. Also, inadequate sanitary facilities such as insufficient number of clean and well-maintained restrooms (52.7%), poor waste management system as a result of insufficient waste collection and disposal services on campus (46.0%) as a result of lack of strict enforcement of sanitation rules and policies (41.8%) all were major contributing factors. Conclusions: Accommodation and sanitation facilities in halls and hostels were found to be inadequate. Some reasons for the poor state of some of the facilities found in our study includes absent sanitation rules and policies on campus, lack of awareness campaigns or programs on campus to promote better sanitation behaviours, among others; were found to contribute significantly to the poor state of sanitation on campus.